Study Correlation and Interaction Effect Among Emotional Intelligence, Organizational Commitment and Job Satisfaction Based of Gender Teachers in Senior High School in Kupang - Delsylia Tresnawaty Ufi; Sutarto Wijono; Adi Setiawan (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: Aim of this research is to analyse the relationship between emotional intelligence, organizational commitment and job satisfaction based on gender of teachers in Senior High Schools in Kupang city Design/methodology/approach: This study had a population of 419 teachers who were civil servants and who had received lecturer certification. The sampling technique used was proportionate random sampling and got a total of 116 teachers. Data analysis techniques used multiple correlation analysis and two way analysis of variance (ANOVA), and different tests. Findings: There are factors related to job satisfaction, namely organizational commitment and all three aspects as well as emotional intelligence with all three aspects. and there is an influence of the interaction of these factors with job satisfaction, and female and male teachers do not have differences in job satisfaction. Research limitations/implications: Result of this research can be used as reference of policy in school in order to increase teachers satisfaction based on gender. Practical implications: Teachers can feel satisfied at work because of work commitments and how they can assess, use and manage emotions. There is also a feeling of satisfaction in working between female and male teachers. Paper type: This study is categorised as a case study.